Toughness of natural rubber compounds under biaxial loading. (November 2015) - Caimmi, Francesco; Calabrò, Roberto; Briatico-Vangosa, Francesco; Marano, Claudia; Rink, Marta
Highlights: Toughness of natural rubber compounds was studied under biaxial loading. A very strong dependence of toughness on the load biaxiality was found. This was correlated with strain induced material anisotropy. The phenomenon of "sideways crack propagation" was also investigated. It was shown to remove any significant stress concentration at the crack main tip. Abstract: Strain induced molecular orientation effect on the fracture toughness of natural rubber based compounds was studied under biaxial loading conditions, using non-linear elastic fracture mechanics. The J -integral at fracture was evaluated using the finite element method. Fracture toughness can be severely influenced by strain induced molecular orientation up to a material dependent threshold, above which toughness becomes constant. The effect of the fracture phenomenology shown by two carbon black filled compounds, for which propagation is preceded by branching at the tip (sideways crack propagation), is shown to remove any significant stress concentration at the original crack tip, enhancing the apparent fracture resistance.